Sociale mediers rolle i politisk kommunikation: et litteraturstudie - Schwartz, Sander Andreas (Politik, 2019)
This study is a systematic literature review of research on social media and political communication from political parties or politicians in parliament. The literature review is narrowed down further to focus on European studies. The review sorts studies into three thematic categories: political sender, citizen engagement and public actors. The study finds that papers are mostly pessimistic about the democratic influence of social media. This might be because studies have been looking for a social media revolution rather than slow evolution over time. The paper goes on to divide studies according to digital methods using digital trace data or traditional methods or a combination of both. The literature review presents the advantages of each approach and further highlights the potential of mixed and multiple methods. Finally, the literature review highlights recent issues with collecting data through platform API and argues that the field should be careful about relying too heavily on this collection approach in the future as social media platforms are starting to restrict access to digital trace data.